2020
DOI: 10.1039/c9fo02992c
|View full text |Cite
|
Sign up to set email alerts
|

Study of the alleviation effects of a combination of Lactobacillus rhamnosus and inulin on mice with colitis

Abstract: Ulcerative colitis (UC) is a common inflammatory bowel disease (IBD) that has serious harmful effects on human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 70 publications
1
53
1
Order By: Relevance
“…Proteobacteria was reported to be the main phylum of pathogenic bacteria, which promoted the production of excessive pro-inflammatory cytokines and related to IBD pathogenesis (24,42). Akkermansia was a confirmed probiotic with anti-inflammatory effect by improving neutrophil infiltration and alleviating intestinal inflammation (44)(45)(46). Bifidobacteria could exert an anti-inflammatory effect through induction of intestinal IL-10 and protect from Th1driven inflammation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria was reported to be the main phylum of pathogenic bacteria, which promoted the production of excessive pro-inflammatory cytokines and related to IBD pathogenesis (24,42). Akkermansia was a confirmed probiotic with anti-inflammatory effect by improving neutrophil infiltration and alleviating intestinal inflammation (44)(45)(46). Bifidobacteria could exert an anti-inflammatory effect through induction of intestinal IL-10 and protect from Th1driven inflammation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that Lactobacillus rhamnosus combined with inulin can reduce DSS-induced colitis, reduce pathological damage of colon tissue, reduce DAI score, regulate the expression of inflammatory cytokines, and have anti-inflammatory effects on mice with enteritis. 25 Therefore, this study established a colitis animal test model to preliminarily explore the ability of a synbiotic composed of L. fermentum HFY06 and arabinoxylan to alleviate colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Last year, researchers found that the pasteurized A. muciniphila or one of its specific outer membrane proteins can alleviate colitis and prevent the occurrence of colitis-associated colorectal cancer by modulating the levels of CD8 + cytotoxic T lymphocytes [ 43 ]. A. muciniphila can also exert an anti-inflammatory effect by preventing neutrophil infiltration and reducing intestinal inflammation [ 44 ]. In this study, HBBG intake significantly increased the relative abundance of A. muciniphila in the intestine.…”
Section: Discussionmentioning
confidence: 99%